Predictors of 6-month and 3-year outcomes after psychological intervention for psychogenic non epileptic seizures. (March 2016) - Duncan, Roderick; Anderson, James; Cullen, Breda; Meldrum, Steven
Highlights: Audit of results of psychological intervention for PNES. 53.1% of patients free of seizures at 6 months. Best predictor of good outcome was locus of control. No good predictors of long term outcome. Abstract: Purpose: To determine outcome and its predictors following psychological intervention in people with Psychogenic Non-Epileptic Seizures (PNES) Methods: Prospective audit of 89 consecutive patients. PNES were recorded at baseline (initial psychology appointment), at 6 months and 3 years post the initial appointment. Six-month data was obtained by face-to-face interview, while 3-year data was obtained by contacting general practitioners and by postal survey. Results: Eight patients had stopped having PNES at the first appointment and were discharged. At 6-month follow up 43/81 patients (53.1%) were free of seizures. Predictors of cessation of seizures were: patient employed (OR 4.48, p = 0.004), short waiting time for intervention (OR 0.94, p = 0.018), the patient feeling they had some control over the seizures (OR 3.30, p = 0.021), and an internal locus of control ((OR 7.46, p = 0.001). Outcomes at 3 years based on patient report were available in 32/81 patients (36%). 11/32 patients reported being free of seizures. 50/65 patients were not accessing any healthcare for seizures. There were no significant predictors of either outcome among the variables collected. Conclusion: Just over half of our patients reported being free of seizures following intervention. Being employed predicted good outcome, but the best predictor of being seizure free at 6 months was having an internal locus of control. This may be useful practically and requires further study. No good predictors of long-term outcome were found, possibly because of loss to follow up